Probe‐Molecule‐Assisted NMR Spectroscopy: A Comparison with Photoluminescence and Electron Paramagnetic Resonance Spectroscopy as a Characterization Tool in Facet‐Specific Photocatalysis. Issue 1 (23rd December 2016) - Peng, Yung‐Kang; Fu, Yingyi; Zhang, Li; Teixeira, Ivo F.; Ye, Lin; He, Heyong; Tsang, Shik Chi Edman
Abstract: Photoluminescence (PL) and EPR spectroscopy are the two most commonly used techniques to evaluate surface oxygen vacancies (VO surface ) on photoactive transition metal oxides. However, these techniques have shortcomings in the characterization of facet‐dependent catalysis. Here, we used the chemical adsorption of a 31 P‐containing probe molecule to obtain the distribution/concentration of VO surface as well as other surface features (hydroxyl groups) of ZnO by using 31 P magic‐angle spinning NMR spectroscopy. This facet‐specific technique not only makes cross‐literature comparison feasible but also provides more comprehensive information to lead to a further understanding of the photocatalytic mechanism. Abstract : Probe it : With the assistance of a 31 P‐containing molecule as a chemical probe, the surface distribution/concentration of surface oxygen vacancies and −OH of ZnO nanoparticles can be obtained by using 31 P magic‐angle spinning NMR spectroscopy. This technique provides more comprehensive information than the commonly used but deficient photoluminescence and EPR spectroscopy and leads to the understanding of the photocatalytic decomposition of methylene blue over different faceted ZnO crystallites.